Enriched Environment Attenuates Pyroptosis to Improve Functional Recovery After Cerebral Ischemia/Reperfusion Injury - Liu, Jingying; Zheng, Jun; Xu, Yang; Cao, Wenyue; Wang, Jinchen; Wang, Biru; Zhao, Linyao; Zhang, Xin; Liao, Weijing (Frontiers in Aging Neuroscience, 2021)
Enriched environment (EE) is a complex containing social, cognitive, and motor stimuli. Exposure to EE can promote functional recovery after ischemia/reperfusion (I/R) injury. However, the underlying mechanisms remained unclear. Pyroptosis has recently been identified and demonstrated a significant role in ischemic stroke. The purpose of this study was to explore the effect of EE on neuronal pyroptosis after cerebral I/R injury. In the current study, middle cerebral artery occlusion/reperfusion (MCAO/R) was applied to establish the cerebral I/R injury model. Behavior tests including the modified Neurological Severity Scores (mNSS) and the Morris Water Maze (MWM) were performed. The infarct volume was evaluated by Nissl staining. To evaluate the levels of pyroptosis-related proteins, the levels of GSDMD-N and nod-like receptor protein 1/3 (NLRP1/3) inflammasome-related proteins were examined. The mRNA levels of IL-1β and IL-18 were detected by Quantitative Real-Time PCR (qPCR). The secretion levels of IL-1β and IL-18 were analyzed by ELISA. Also, the expression of p65 and p-p65 were detected. The results showed that EE treatment improved functional recovery, reduced infarct volume, attenuated neuronal pyroptosis after cerebral I/R injury. EE treatment also suppressed the activities of NLRP1/NLRP3 inflammasomes. These may be affected by inhabiting the NF-κB p65 signaling pathway. Our findings suggested that neuronal pyroptosis was probably the neuroprotective mechanism that EE treatment rescued neurological deficits after I/R injury.